Fraud and forensic accounting: knowledge and risk assessment task performance in Malaysian public sector – conceptual study - Popoola, Oluwatoyin Muse Johnson; Che Ahmad, Ayoib; Samsudin, Rose Shamsiah (Global Science & Technology Forum Pte Ltd., Singapore, 2014)
The PwC’s 2011 Global economic crime survey confirms the fact that loss due to economic crime in Malaysia is on the increase and requires immediate intervention. The Malaysian government vision 2020 to be a developed nation with the drive: “People first, performance now” [1] will require high level acquisition and adoption of technology as a business facilitator, new legislation, and increase in the activities of government offer new opportunities for fraud perpetrators and forensic accountants. In anticipation of these challenges, this paper discusses the need for a forensic accountant knowledge on task performance fraud risk assessment in the Malaysian public sector. It also creates awareness to stakeholders fighting fraud in the public sector to the understanding of fraud mechanism and how to deal with fraudsters. The objective of the study is to examine the relationship between knowledge and fraud risk assessment task performance in the office of the Accountant general and Auditor general of Malaysia which has the potential to usher in the best global practices in fighting fraud in the Malaysian public sector.